An assessment of thermocline-control methods for packed-bed thermal-energy storage in CSP plants, Part 1: Method descriptions. (15th January 2019) - Geissbühler, L.; Mathur, A.; Mularczyk, A.; Haselbacher, A.
Highlights: Origins and negative effects of thermocline degradation are described. Prior work on passive and active methods for tackling thermocline degradation is reviewed. Term "thermocline control" for active methods is introduced. Three methods for thermocline control are described in detail. Two of these methods are derived from prior works, the third method based on mixing is novel. Abstract: Thermocline thermal-energy storage (TES) suffers from so-called thermocline degradation, which refers to the flattening of temperature gradients in the TES with successive charging-discharging cycles. Thermocline degradation increases the variations of the heat-transfer fluid (HTF) outflow temperatures, decreases storage utilization factors, and increases specific TES material costs. Methods that prevent or reduce thermocline degradation by changing the operation of the storage are called thermocline-control (TCC) methods. The assessment of TCC methods is the main objective of this work. Three TCC methods that were chosen for this assessment are described in this paper. Two methods, based on either extracting or injecting HTF through ports, were derived from previously published methods while the third method, based on mixing multiple HTF streams, one of which is extracted through a port, is novel. In a companion paper (Geissbühler et al., Solar Energy, submitted 2018), the three TCC methods are assessed for air and molten salt as HTF using simulations of stand-alone storages as well as storages integrated into a concentrated solar power plant.